Pobreza, miséria e exclusão. Por um cristianismo sensível - Lopes, Claudinei Jair (Revista eclesiástica brasileira, 2009)
Now in the beginning of the third millennium we live a terrible war of poverty, misery and exclusion. A faceless war that deforms and kills the face of God present in history. Before this, a question imposes itselt: what sustains such situation and what does it reveal to Christianity? Placing it in the current economic model that sustains and feeds the logic of insensibility, the author presents the challenge for Christianity, follower of the Gospel of Life revealed in Jesus of Nazareth: to be sensitive to the clamor for Life that springs from so many voices.